Amylolytic activities of Amazonian rhizobacteria in culture media containing corn starch (Zea mays L.) or babassu flour (Orbignya phalerata Mart) (Research, Society and Development, 2022)
Assessing the presence of amylases in rhizobacteria is very important, since starch can be used as a raw material for bioproducts production of economic importance. Emphasis should be given to those that can use the starch from babassu flour, strengthening the production chain of this palm tree ignored by the Amazon bioeconomy. For this purpose, 40 rhizobacteria were tested in a culture medium containing corn starch or babassu flour. All showed the ability to grow in the two-culture media, but there was a very large difference between them, shown by the diameters of their colonies on the fifth day of growth. Of the 40 rhizobacteria, 19 showed amylase production in the medium containing corn starch and 16 in the medium containing babassu flour. Amylolytic bacteria have the potential to be used in starch degradation for biotechnological purposes. More studies are needed to select the best ones for this purpose, such as the effect of pH, temperature, and the efficiency of converting corn starch and babassu flour into products with desirable biotechnological characteristics.